Hubungan Kesadaran Metakognitif terhadap Keterampilan Proses menggunakan Model Pembelajaran Inkuiri Terbimbing Berbantuan Lembar Kerja Mahasiswa - Eka Fitriana Hamsyah; Gustina; Fandi Ahmad; St. Humaerah Syarif; Nur Amaliah Akhmad (Jurnal Kreatif Online, 2021)
This study is ex-post-facto research that aims to determine whether there is a correlation between metacognitive awareness and process skills using a guided inquiry learning model assisted by students’ worksheets. The population of this research is the third-semester student of the biology education study program at STKIP PI Makassar. Sample selection is selected randomly. The research instrument that was used to measure process skills was 20 numbered objective questions. Process skill indicators are observing, classifying, predicting, measuring, inferring, and communicating. A total of 52 statement items (positive and negative) Metacognitive Awareness Inventory (MAI) were used to measure students’ metacognitive awareness. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. Data testing using linear regression test of one independent variable with SPSS 17 program. Based on the results of the linear regression test, it was obtained that the value of R = 0,111 and R square = 0,012. This shows that there is a correlation between metacognitive awareness and process skill, even though it has a very low category with the percentage of impaired metacognitive awareness of 0,12%.